2017
DOI: 10.1103/physrevb.95.035138
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of a heavy-fermion U(Ru0.92Rh0.08)2Si2 single cr

Abstract: We report the crystal structure and highly anisotropic magnetic, transport, and thermal properties of an exceptionally good single crystal of U(Ru 0.92 Rh 0.08 ) 2 Si 2 , prepared using a modified Czochralski method. Our study, that also includes neutron diffraction results, shows all the heavy-fermion signatures of pristine URu 2 Si 2 ; however, the superconductivity, hidden order, and remnant weak antiferromagnetic orders are absent. Instead, the ground state of the doped system can be classified as a spin l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…1), to establish the lattice constants and orientation matrix of the crystal with respect to the laboratory system and to evaluate the magnetic moment magnitudes. We found that the intensities recorded in zero field agree well after necessary absorption and extinction corrections with the crystal structure parameters determined previously [13].…”
supporting
confidence: 55%
See 4 more Smart Citations
“…1), to establish the lattice constants and orientation matrix of the crystal with respect to the laboratory system and to evaluate the magnetic moment magnitudes. We found that the intensities recorded in zero field agree well after necessary absorption and extinction corrections with the crystal structure parameters determined previously [13].…”
supporting
confidence: 55%
“…The system does not order magnetically, so only short-range order (SRO) characterized by Q 3 at low temperatures is detected [13]. For fields up to 58 T applied along the a axis (not shown) the magnetization is tiny and increases linearly with field.…”
mentioning
confidence: 99%
See 3 more Smart Citations